Prove or disprove $$I=\sum_{n=2}^{\infty}\left(1+\dfrac{1}{3^2}+\dfrac{1}{5^2}+\cdots+\dfrac{1}{(2n-1)^2}\right) \binom{2n}{n}\dfrac{1}{2^{2n}(2n+1)}=\dfrac{\pi^3}{48}-\dfrac{1}{6}$$

My try: since $$\binom{2n}{n}\dfrac{1}{2^{2n}(2n+1)}=\dfrac{(2n)!}{(n!)^2\cdot 2^{2n}(2n+1)}=\dfrac{(2n-1)!!}{2^n\cdot n!(2n+1)}$$

so $$I=\sum_{n=2}^{\infty}\left(\sum_{j=1}^{n}\dfrac{1}{(2j-1)^2}\cdot\dfrac{(2n-1)!!}{2^n\cdot n!(2n+1)}\right)$$

Then I can't continue.Maybe this sum have closed form,Thank you

  • 4
    $\begingroup$ Hint: Fubini. (Unrelated: I noticed that you often call "My idea" a pragraph which does not describe an "idea", at most a trivial rewriting of the question leading nowhere nearer to a solution. In such cases, you might want to adopt another terminology?) $\endgroup$ – Did Jun 14 '14 at 8:38
  • $\begingroup$ Oh,@OmranKouba,Thank you very much! $\endgroup$ – math110 Jun 14 '14 at 15:37

Lemma. For $x\in[-1,1]$, we have $$ \frac{1}{6}(\arcsin x)^3=\sum_{n=1}^\infty a_nx^{2n+1} $$ with $$a_n=\left(\sum_{j=1}^n\frac{1}{(2j-1)^2}\right)\binom{2n}{n}\frac{1}{2^{2n}(2n+1)}.$$

Proof. First, we will suppose that $x \in(-1,1)$. Recall that, $$\arcsin x= \sum_{n=0}^\infty \binom{2n}{n}\frac{x^{2n+1}}{2^{2n}(2n+1)}\tag{1}$$ Now, let $f(x)=\frac{1}{6}(\arcsin x)^3$. Clearly, $$\sqrt{1-x^2}f'(x)=\frac{1}{2}(\arcsin x)^2,$$ hence $$(1-x^2)f''(x)-x f'(x)= \arcsin x \tag{2}$$ Now, if $\sum_{n=0}^\infty a_nx^{2n+1}$ (with $a_0=0,a_1=1/6$,) is the power series expansion of $f$ then replacing in $(2)$ we get $$ \sum_{n=0}^\infty((2n+3)(2n+2)a_{n+1}-(2n+1)^2a_n)x^{2n+1}=\arcsin x $$ comparing with $(1)$ we see that $$ (2n+3)(2n+2)a_{n+1}-(2n+1)^2a_n=\binom{2n}{n}\frac{1}{2^{2n}(2n+1)} $$ This is equivalent to $$ 2^{2n}\frac{(2n+3)(2n+2)}{(2n+1)\binom{2n}{n}}a_{n+1}-\frac{(2n+1)2^{2n}}{\binom{2n}{n}}a_n=\frac{1}{(2n+1)^2} $$ or $$ 2^{2n+2}\frac{(2n+3)}{\binom{2n+2}{n+1}}a_{n+1}-\frac{(2n+1)2^{2n}}{\binom{2n}{n}}a_n=\frac{1}{(2n+1)^2} $$ adding these equalities for $n=0,1,\ldots,m-1$ we get $$ 2^{2m}\frac{(2m+1)}{\binom{2m}{m}}a_{m}= \sum_{n=0}^{m-1}\frac{1}{(2n+1)^2} $$ which is the desired formula for $a_m$. Finally, noting that $a_n=\mathcal{O}(n^{-3/2})$, we conclude that the power series $\sum a_mx^{2m+1}$ does converge as $x$ tend to $+1$ or $-1$. So by Abel's theorem we conclude that this power series converges to $f(x)$ also for $x=1$ and $x=-1$, and the lemma follows.$\qquad\square$

In particular, taking $x=1$ we obtain $$ \frac{\pi^3}{48}=\sum_{n=1}^\infty\left(\sum_{j=1}^n\frac{1}{(2j-1)^2}\right)\binom{2n}{n}\frac{1}{2^{2n}(2n+1)} $$ taking away the first term, we obtain $I=\frac{\pi^3}{48}-\frac{1}{6}$.

Also, taking $x=\frac{1}{2}$ we get $$ \frac{\pi^3}{648}=\sum_{n=1}^\infty\left(\sum_{j=1}^n\frac{1}{(2j-1)^2}\right)\binom{2n}{n}\frac{1}{2^{4n}(2n+1)} $$

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.